Contemporary perspectives on electrical processes in different types of secretory cells and their stress-induced changes - Тарасова, Катерина; Karvatsky, Ігор (Psychosomatic Medicine and General Practice, 2025)
Relevance. Electrical processes in secretory cells are crucial for their function, and studying these processes, along with their changes under stress, can provide insights into various physiological and pathological conditions. Understanding how electrical signals and related proteins change under stress can reveal potential therapeutic targets for medicines and will contribute to the creation of physiologically sound ways to control cellular functions. Aim. Analysis and generalization of current knowledge about the mechanisms of electrical processes in secretory cells and their stress-induced changes and identification of promising directions for future research. Materials and methods. Scientific publications of electrophysiological research results were presented in peer-reviewed scientific publications, mainly within the last ten years. Conclusions. Although research results are not always unambiguous, it has been established that the nature of the electrical activity of secretory cells affects exocytosis. Therefore, the generalization of key mechanisms and interpretation of changes in electrical processes in secretory cells under stress require further research on various models.